Beta‐blocker use and mortality among patients with systolic heart failure and pacemaker rhythm - Andrew S. Perry; Aldo P. Maggioni; Luigi Tavazzi; Wayne C. Levy (ESC Heart Failure, 2023)
Abstract Aims Beta‐blockers are proven to improve survival among patients with heart failure with reduced ejection fraction. Their efficacy in patients with heart failure with reduced ejection fraction and pacemaker devices has not been demonstrated. Our aim was to test the hypothesis that beta‐blocker therapy is associated with improved survival in patients with chronic heart failure and a pacemaker rhythm on electrocardiogram (ECG). Methods and results This is a post hoc analysis from the GISSI‐HF randomized clinical trial. We evaluated efficacy of beta‐blockers by creating Cox proportional hazards models adjusting for pacemaker rhythm and heart rate, among other variables. Interactions between pacemaker rhythm, heart rate, and beta‐blocker were also examined. Of the 6975 patients enrolled in the GISSI‐HF trial, 813 (11.7%) had a pacemaker rhythm on baseline ECG. Of these 813 patients, 511 (62.9%) were receiving beta‐blocker therapy. The effect of beta‐blocker therapy on mortality was assessed using multivariable Cox proportional hazards adjusted for 27 co‐variates. In the whole cohort, beta‐blocker therapy was significantly associated with reduced mortality (hazard ratio 0.79 [0.72–0.87], P < 0.001), without interaction between beta‐blockers, pacemaker rhythm and heart rate. Beta‐blocker therapy was beneficial in the sub‐group restricted to baseline pacemaker rhythm (hazard ratio 0.62 [0.49–0.79], P < 0.001). Conclusions Beta‐blocker therapy is associated with improved survival among patients with heart failure and a pacemaker rhythm on ECG. Further studies are necessary to analyse differences between atrial and ventricular pacemakers.